Effects of Mathematics Learning Activity Management Using Cooperative Learning STAD Technique with The Polya’s Problem Solving Process of Prathomsuksa 4 Students - Onsri, Benjaluk; Jaradrawiwat, Sirawan; Jenjit, Apunchanit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to compare mathematics learning achievement of students in Prathomsuksa 4 before and after studying learning activity management using cooperative learning STAD technique with the Polya’s 2)mathematics problem solving ability of students in Prathomsuksa 4 befor and after learning activity management using cooperative learning STAD technique with the Polya’s, 3) to study team work of studying of students in Prathomsuksa 4 studying activity management using cooperative learning STAD technique with the Polya’s. The sample groups in this research consisted of 18 Prathomsuksa 4 studying students in Buriram Province, The cluster random sampling method was used in selecting students in experiment group. The research instrument were 1) the lesson plans the learning activity management using cooperative learning STAD technique with the Polya’s, 2) a learning achievement test, 3) a problem solving ability test, 4) team work behaviors observation forms with confidence = 0.85. The data was analyzed by the use of Mean, Median, and the Paired T-test Dependent. The research results were as follows : 1. Students mathematics learning achievement of scores in the using learning activity management using cooperative learning STAD technique with the polya’s was significantly higher than the pre-test at .05 level. 2. The post-test scores of student’ mathematics problem solving ability in the using learning activity management using cooperative learning STAD technique with the polya’s was significantly higher than the pre-test at .05 level. 3. The team work of Prathomsuksa 4 the polya’s were at a good level.